The Gut Microbiome and the Pathophysiology of Functional Gastrointestinal Disorders with Psychiatric Symptoms - Cristina Gabriela Schiopu; Cristinel Stefanescu; Alexandra Bolos; Smaranda Diaconescu; Georgiana-Emmanuela Gilca-Blanariu; Gabriela Stefanescu (Perspective of Recent Advances in Medical Research Vol. 11, 2023)
The present article proposes a detailed description of the physiology of the microbiome-gut-brain axis, the pathophysiology of the functional gastrointestinal disorders and the proportional presence of psychiatric comorbidities. Also, current perspectives for therapeutical management are described, by revealing the latest studies in the field and the clinical relevance of their results in both adult and pediatric population. The gut-brain axis mechanism and the microbiome form a complex ecosystem. The intestinal bacteria population may be the key to modulate not only digestive disorders but also, neurologic and psychiatric pathologies. As functional gastrointestinal syndromes are often accompanied by affective and cognitive symptoms, they may be the most relevant pathophysiological argument of the importance of the gut-brain axis.